2018
DOI: 10.1038/s41430-018-0198-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy predictors of a 2-month exclusive enteral nutrition for inducing remission of active Crohn’s disease

Abstract: In order to identify the factors that could predict the efficacy of exclusive enteral nutrition (EEN) in inducing remission of active CD. Baseline clinical and laboratory covariates were correlated with the outcome (clinical remission) of EEN in active CD (CDAI ≥150) by both univariable and multivariable analyses. A total of 67 from a consecutive of 136 active CD patients were enrolled. L4b (from treitz ligament to distal 1/3 ileum) involvement was negatively and high serum albumin (≥35 g/L) was positively ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We did not examine in detail the clinical, serological immune response, genetic or microbiome signatures that predict therapeutic response. Recently, Meng Xue et al con rmed that L4b involvement was negative and that high serum ALB was positively associated with clinical remission [22]. Casey M A et al also con rmed that bacterial taxa and functions are predictive of remission following exclusive enteral nutrition in pediatric CD patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…We did not examine in detail the clinical, serological immune response, genetic or microbiome signatures that predict therapeutic response. Recently, Meng Xue et al con rmed that L4b involvement was negative and that high serum ALB was positively associated with clinical remission [22]. Casey M A et al also con rmed that bacterial taxa and functions are predictive of remission following exclusive enteral nutrition in pediatric CD patients [23].…”
Section: Discussionmentioning
confidence: 99%
“… 29 Xue et al showed that the efficacy rate of EEN was 67.2% for CD patients in our center. 30 Adherence to medication is very important for the treatment of chronic diseases. 31 High adherence is associated with positive health outcomes.…”
Section: Discussionmentioning
confidence: 99%